Adaptation‐Proof SARS‐CoV‐2 Vaccine Design. (3rd October 2022) - Vishweshwaraiah, Yashavantha L.; Hnath, Brianna; Rackley, Brendan; Wang, Jian; Gontu, Abhinay; Chandler, Morgan; Afonin, Kirill A.; Kuchipudi, Suresh V.; Christensen, Neil; Yennawar, Neela H.; Dokholyan, Nikolay V.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) surface spike glycoprotein—a major antibody target—is critical for virus entry via engagement of human angiotensin‐converting enzyme 2 (ACE2) receptor. Despite successes with existing vaccines and therapies that primarily target the receptor binding domain (RBD) of the spike protein, the susceptibility of RBD to mutations provides escape routes for the SARS‐CoV‐2 from neutralizing antibodies. On the other hand, structural conservation in the spike protein can be targeted to reduce escape mutations and achieve broad protection. Here, candidate stable immunogens are designed that mimic surface features of selected conserved regions of spike protein through "epitope grafting, " in which the target epitope topology is presented on diverse heterologous scaffolds that can structurally accommodate the spike epitopes. Structural characterization of the epitope‐scaffolds showed stark agreement with computational models and target epitopes. The sera from mice immunized with engineered designs display epitope‐scaffolds and spike binding activity. The utility of the designed epitope‐scaffolds in diagnostic applications is also demonstrated. Taken all together, this study provides an important methodology for targeting the conserved, non‐RBD structural motifs of spike protein for SARS‐CoV‐2 epitope vaccine design and demonstrates the potential utility of "epitope grafting" in rational vaccine design. Abstract : The majority of SARS‐CoV‐2 vaccines currently being developed or deployed target the spike receptor binding domain (RBD); the mutation‐prone nature of RBD alters the effectiveness of the RBD region‐centered vaccines. Here, to combat the adaptability of the virus, candidate immunogens that target the structural conservation of the spike protein are designed. The results provide important methodology for targeting the conserved, non‐RBD structural motifs of spike protein of SARS‐CoV‐2, and an immune‐focused approach in pan‐sarbeco and universal coronavirus rational vaccine design.